Use of alcoholic preparation in surgical hand antisepsis: an integrative review (Research, Society and Development, 2022)
Objective: To compare the immediate antimicrobial efficacy and residual effect of alcoholic preparations in relation to traditional products for surgical hand antisepsis, evidenced by the scientific literature. Methods: This is an integrative literature review, carried out from September 2020 to January 2021. The study selection strategy was to search for publications indexed in MEDLINE, UPTODATE, LILACS, SCIELO. The following inclusion criteria were adopted: articles published in Portuguese, English and Spanish, between the years 2010 to 2020 and that aproached the theme of the study. Thesis, dissertations and duplicate articles were excluded. Based on these criteria, 7 scientific materials were found. Results: Alcoholic preparations have a shorter application / contact time compared to traditional products, due to their quick antimicrobial effect and longer lasting residual effect, which optimizes the time of professionals and hospital resources. The disadvantages are related to the dryness effect, burning sensation in hands and their volatile nature, which can be controlled through use of emollients or other conditions, in addition to special attention to the control of the volatile nature. The use of AP eliminates time spent when compared to brushing with chlorhexidine and represents a lower cost in terms of water use, also generating a reduction in ecological impacts regarding the use and disposal of brush residues and a reduction in water consumption. Conclusion: the alcoholic antiseptic solution brings more benefits in its use when compared to traditional techniques and its adherence in health institutions in Brazil should be stimulated considering the cost-benefit compared to the brushing technique, being essential the involvement of managers and assistance teams for changing practice.